Business Strategies To Increase Sales In Galery Jam Tangan Bandar Lampung In The Era Of The Covid 19 - Vina Putri Agustiyani; Agus Salim; Riki Renaldo (Dinar Islamic Review, 2022)
This research has the objective of knowing the right business strategy to be able to increase sales volume and find out what are the Strengths, Weaknesses, Opportunities and Threats owned by the Bandar Lampung Watch Gallery. The data is presented descriptively..qualitatively to determine the external and internal environment. The acquisition of alternative strategies is obtained from the calculation of the SWOT matrix. Analysis of the external planning variable shows the results of a weighted score of 2.59, this means that the company's management reaction to the external environment is below the average standard measurement scale. Analysis of internal planning variables shows that the weighted score is 2.57, this means that the company's management reaction to the internal environment is below the average standard measurement scale. Based on the results of the IFAS and EFAS matrix analysis, it is known that the strategy used is the stability strategy, the stability strategy is a plan that is implemented without changing the plan that has been set. The Bandar Lampung Watch Gallery maintains profit stability by seeking to reduce and suppress costs or expenses to deal with declining sales, and this strategy is temporary or short term.